In the face of the sun : a novel - Bryce, Denny S. (Kensington Publishing Corp., 2022)
To escape an abusive marriage, Frankie Saunders flees across the country to Los Angeles with her reckless, profane Aunt Daisy, who will do whatever it takes to settle old scores and resolve the past--no matter what the damage, forcing Frankie to make some hard choices.